Analisis Kebutuhan Parkir Pasar Inpres Lipa Kalabahi, Kabupaten Alor - Maubara, Lyani Herlina Ferdita; Sir, Tri M.W.; Frans, John H. (Universitas Nusa Cendana, 2023)
Parking is a problem often encountered, especially in areas with high activity, such as markets. With the community's needs that must be met, the government provides a market for the people of Alor, namely the Inpres Lipa market. It offers good service and facilities, one of which is by providing a parking lot. However, because the parking area is often used for selling areas, several vehicles are parked on the shoulder of the road, causing traffic jams around the market. This research aims to determine the characteristics of parking and parking needs at present and in the next five years. The method used in this study is descriptive quantitative to describe parking characteristics and parking needs in the next five years. The analysis results are as follows: The maximum vehicle volume for motorcycles is 322 vehicles, and the maximum volume for cars is 52 vehicles, while the minimum vehicle volume for motorcycles is 177 vehicles, and cars are 23 vehicles. The highest accumulation of parking for motorbikes was 74 vehicles, while there were nine vehicles for cars. The minimum parking duration for motorbikes is 0,03 hours, and for cars is 0,05. The maximum duration of the motorbike is 1,095 hours, and the maximum duration of the car is 1,09 hours. The maximum average parking duration for motorbikes is 1,096 hours, the maximum average time for cars is 1,001 hours, the average period for motorcycles is a minimum of 0,43 hours, and the average period for cars is a minimum of 0,4 hours. Parking capacity for motorbikes is 79 SRP, and cars are 10 SRP. The parking index for motorbikes and cars is <100%, meaning parking facilities are not problematic. The highest current need for parking is 44 vehicles, with a land area of ​​66 m2, and five cars, with an area of ​​62,5 m2. The projected demand for parking in 2027 for motorbikes is 93 SRP of parking space required 139,5 m2, and for cars, 11 SRP of parking space required 135,7 m2.